DETERMINANTS OF FOOD CHOICE IN OBESITY - Nur Aisiyah Widjaja; Rendi Aji Prihaningtyas (Universitas Airlangga, 2020)
ABSTRACTThe prevalence of obesity is increasing at all ages in Indonesia. Obesity does not only cause health complications, such as dyslipidemia, cardiovascular disease, cancer, and osteoarthritis but also has a negative effect on a countr’s socioeconomic conditions. Previous studies have explained that food choices affect the incidence of obesity. This literature review aims to explain the factors that influence the food choice related to obesity. Genetic and environmental factors affect the food choice in individuals that can cause obesity. Environmental factors play a major influence on food choice, including peers, family, economic status education environmental conditions, stress, and sedentary behavior. Detection of environmental factors that influence food choice can be one of the strategies to prevent obesity. Key words : Obesity, Diet, Food Preference, Food Choice, Adolescents